Effects of Monosodium Glutamate on 14- to 56-lb Nursery Pigs - A. B. Clark; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; J. C. Woodworth; R. D. Goodband; K. J. Touchette (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 700 nursery pigs (PIC C-29 × 1050 × 1040, initially 13.6 lb BW) were used in a 42-d growth study to determine the effects of monosodium glutamate (MSG; Ajinomoto Heartland, LLC, Chicago, IL) on growth performance. Pigs were fed 1 of 5 dietary treatments: 0, 0.5, 1.0, 1.5, or 2.0% MSG. Experimental diets were fed in three phases from d 0 to 14, 14 to 28, and 28 to 42. Phase 1 was pelleted and phases 2 and 3 were fed in meal form. Diets were formulated to balance Na and Cl content with increasing MSG using salt, sodium bicarbonate, and potassium chloride. Pigs were weaned at approximately 21-d of age and allotted to pens, which were then allotted to treatment according to BW in a randomized complete block design. There were 14 replications per treatment and initial BW was used as a covariate. There were no significant differences between dietary treatments for ADG or ADFI within any phase or for the overall nursery period. Increasing MSG did not affect F/G during phase 1; however, it tended (quadratic, P<0.079) to improve F/G in phase 2, but resulted in poorer F/G (linear, P<0.002) for phase 3. For the overall nursery period, F/G tended (quadratic, P<0.092) to be poorer with increasing MSG. There were no significant differences among dietary treatments for intermediate or final BW. Results from this study indicate that MSG did not influence overall nursery pig growth performance. Additional research may be necessary to determine the appropriate dietary inclusion of MSG and its role during the post-weaning period.
Keywords: monosodium glutamate; nursery pig; growth